An Efficient Adaptive Anticollision Algorithm Based on 4-Ary Pruning Query Tree. (21st December 2013) - Zhang, Wei; Guo, Yajun; Tang, Xueming; Cui, Guohua; Wu, Longkai; Mei, Ying
Abstract : In radio frequency identification system (RFID), the efficiency in which the reader identifies multiple tags is closely related to the methods to solve the collision of multiple tags. At present, a reasonable solution is the introduction of 4-ary query tree (or n -ary query tree) to reduce the collision time slots and additional query is used to decrease idle timeslots. The advantage of a 4-ary tree anti-collision algorithm is that it is able to reduce collision timeslots, but it also increases the idle timeslots. To reduce these excessive idle timeslots the 4-ary tree anticollision algorithm brings, an anti-collision algorithm based on adaptive 4-ary pruning query tree (A4PQT) is proposed in this paper. On the basis of the information of collision bits, some idle timeslots can be eliminated through pruning the 4-ary tree. Both theoretical analysis and simulation results support that A4PQT algorithm can significantly reduce recognition time and improve throughput of the RFID system.